Waiting for ICU admission may increase the risk of death-A plea for better resource organization - Castro, Silvia (2020)
Background Mortality is high in critically ill patients. In order to study the risk factors associated with mortality in these patients, we conducted an observational retrospective study in the general Intensive Care Unit (ICU) of Faro Hospital. Methods All patients discharged from the general ICU in the year 2015 were evaluated for inclusion. Mortality was characterized in the first 48 hours of ICU stay, at the time of discharge from ICU, and at discharge from hospital. Collected variables included demographic variables (age), and ICU variables: type of ICU admission (scheduled surgery, urgent surgery, medical and trauma), Simplified Acute Physiology Score (SAPS II), main diagnosis, hospital length of stay (HLS) before ICU (BICULS), in ICU (ICULS) and after ICU (AICULS). Results When comparing survivors with non-survivors, we found that age, disease severity expressed by SAPS II and BICULS were significantly higher in non-survivors. After multivariate regression analysis, BICULS was still significantly associated with mortality in the hospital. Conclusion Further studies are needed to characterize whether this longer BICULS is related to non-modifiable prior conditions or whether it is related to delayed ICU admission, which is a modifiable factor.